Estratégias de suplementação para novilhas nelore recriadas em pastejo no período de transição seca-águas em metanálise de suplementação de bovinos de corte em pastejo - Silva, Lilian Chambó Rondena Pesqueira (2012)
Two experiments were conducted at the Beef Cattle Production of the experimental Farm of Federal University of Mato Grosso, located in Santo Antonio of Leverger - Mato Grosso, with the objective to evaluate the supplementation of energetic, proteic and multiple, on nutritional parameters, performance economic viability of Nelore heifers in growing on Brachiaria brizantha cv. Marandu during dry-rainy transition season. In addition, we performed a metaanalysis study of supplementation of beef cattle in Brazil under grazing systems of Brachiaria brizantha cv. Marandu and Brachiaria decumbens grasses. In Experiment 1, four heifers 12 months old with initial body weight of 189.5 kg, distributed in four paddocks of 0.25 ha each. The design was a 4x4 Latin square (four supplements and four periods of 14 days). The supplements were: energy supplement (ES) protein (PS), multiple (MS), provided the amount of 1 kg animal day-1 in addition to exclusive mineral supplement ad libitum (MM). The concentrate supplementation did not increase (P<0.05) intakes of dry matter and total organic matter and feed. The additional SP provided greater (P<0.05) crude protein (CP), while the SE and SP supplement resulted in greater (P<0.05) ether extract intake. A higher digestibility (P <0.05) DM and total digestible nutrients (TDN) for concentrated supplements (SE, SP and SM). The CP was higher (P<0.05) in animals supplemented with SP and SM. There was a higher digestibility (P<0.05) for the SE and SM as supplements to total carbohydrates (P<0.05) and non-fiber carbohydrates. Immediately before and four hours after supplementation higher concentrations of ruminal NH3-N (P<0.05) were observed for the SM and SP supplements. There were no differences (P>0.05) for serum urea nitrogen (SUN). The use of protein supplement and múltipo provided the best fit of the rumen of heifers during the transition period dry-rainy. In the experiment 2, Twenty heifers with initial body weight of 189.75kg and average initial age of 12 months were used, which were divided into four paddocks of 1.6 ha each. A completely randomized design with five replications and four treatments was used. The experimental design was completely randomized with four replications and five supplements to assess the same supplements used in the experiment 1.The economic evaluation was performed considering the return on invested capital by dividing the profit margin for the total investment involved in the process of supplementation. The average daily gain (ADG) was higher (P<0.10) for animals receiving PS (0,683 kg animal day-1) and MS (0,664 kg animal day-1) supplements in relation to supplement MM (0,481 kg animal day-1). In economic terms was observed a greater return for the PS supplement (4.38%). The use of protein supplementation and multiple promoted higher productive performance of heifers supplemented in the dry-water transition, however the protein supplement resulted in greater economic returns. In meta-analysis were used 66 studies, totaling 287 experimental units, 188 for the dry season and 99 for the rainy season. The information in the sections of material, methods and results of each study were entered into spreadsheets using Microsoft Excel software. Data from experiments were grouped according to type of forage (Brachiaria brizantha and Brachiaria decumbens) and season (dry and wet). First the variables included in the database were analyzed by the Shapiro-Wilk were subsequently analyzed by regression. The crude protein (CP) Foraging time increased ADG for animals grazing on grass Marandu in the dry season (P=0,001) and decumbens in the rainy season (P=0.027). The acid detergent fiber (ADF) in the dry season on grass Marandu (P=0.001) and neutral detergent fiber indigestible (NDFi) in the rainy season in Brachiaria decumbens resulted negative response on this trait. Greater weight gain was obtained with increase in the level of supplementation for cattle grazing palisade grass (P=0.001) and decumbens (P=0.001) at the time of the year with R2 of 0.548 and 0.500 respectively. In the wet season and grazing Brachiaria decumbens was no effect of supplementation level on ADG of animals (P=0.070) and the rainy season there was no effect (P=0,172). The equation was generated for the dry season ADG = 0.110 + 0.590 Level of supplementation (% BW) + 0.0155CP forage (%) and the rainy season ADG=0.501+0.203Level of supplementation (% BW) + 0.0236 CP forage (%). It is concluded that supplementation in the dry season is recommended in the rainy season and supplementation is justified only when you want to gain weight greater than 0.620 kg/day or when the crude protein content of forage is less than 5%. The use of concentrade supplementation is effective in promoting greater total apparent digestibility of dry and does not alter the dry matter intake. The protein supplements and multiple result in a higher concentration of nitrogen in the rumen amonical four hours before and after supplementation. Increased productive performance of heifers grazing dry during the transition period is achieved with water-supply and multiple protein supplement, however, the use of protein supplements provide higher economic return. Through meta-analysis can be concluded that supplementation in the dry season is recommended in the rainy season and supplementation is justified only when you want to gain weight greater than 0.620 kg / day or when the crude protein content of forage is less than 5%.